The Cost of Free Shipping Amazon in the Global Economy - Alimahomed-Wilson, Jake; Reese, Ellen (Pluto Press, 2021)
Amazon is the most powerful corporation on the planet and its CEO, Jeff Bezos, has become the richest person in history, and one of the few people to profit from a global pandemic. Its dominance has reshaped the global economy itself: we live in the age of 'Amazon Capitalism'. 'One-click' instant consumerism and its immense variety of products has made Amazon a worldwide household name, with over 60% of US households subscribing to Amazon Prime. In turn, these subscribers are surveilled by the corporation. Amazon is also one of the world's largest logistics companies, resulting in weakened unions and lowered labor standards. The company has also become the largest provider of cloud-computing services and home surveillance systems, not to mention the ubiquitous Alexa. With cutting-edge analyses, this book looks at the many dark facets of the corporation, including automation, surveillance, tech work, workers' struggles, algorithmic challenges, the disruption of local democracy and much more. The Cost of Free Shipping shows how Amazon represents a fundamental shift in global capitalism that we should name, interrogate and be primed to resist.